2021
DOI: 10.1039/d1tc03495b
|View full text |Cite
|
Sign up to set email alerts
|

High-performance cement/SWCNT thermoelectric nanocomposites and a structural thermoelectric generator device towards large-scale thermal energy harvesting

Abstract: For the first time, the thermoelectric properties of cement/ single-walled carbon nanotubes (SWCNT) nanocomposites over 3, 7, 14 and 28 days of hydration are reported, while a thermoelectric generator device...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…The conductive paths are created by the conductive particles directly in contact with each other as cementitious crystals nucleate during the hydration process and repel SWCNT and nCB to the boundaries. Furthermore, since the distance between the adjacent nanoparticles is diminishing, junctions are formed, enabling electrons to easily pass through this junctions via “hopping” or “tunneling” mechanisms. , The electrical conductivity and the Seebeck coefficient of the organic TE materials are determined by the doping level. Increasing the doping level can lower S while increasing σ.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conductive paths are created by the conductive particles directly in contact with each other as cementitious crystals nucleate during the hydration process and repel SWCNT and nCB to the boundaries. Furthermore, since the distance between the adjacent nanoparticles is diminishing, junctions are formed, enabling electrons to easily pass through this junctions via “hopping” or “tunneling” mechanisms. , The electrical conductivity and the Seebeck coefficient of the organic TE materials are determined by the doping level. Increasing the doping level can lower S while increasing σ.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasonication was performed for 60 min at 25% (∼8 kJ) using a UP400S tip-ultrasonic probe processor (Hielscher Ultrasonics). The SWCNT content was selected based on our previous study , that demonstrated optimum TE performance for the prepared cementitious nanocomposites at 0.5 wt % SWCNT by weight of cement. For the preparation of the hybrid dispersions, nCB was added to the SWCNT solution at various contents (i.e., 0.25, 0.5, 1.0, and 2.0 wt % by weight of cement) under magnetic stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Also, in some cases, during the addition of graphene nanoinclusions, graphite formations occur at grain boundaries via agglomeration during sintering . These secondary phases are detrimental concerning their thermoelectric performance; therefore, nanoinclusions should be chemically inert with the matrix phase. , Carbon allotropes are also famous for their use in cement and organic thermoelectric composites to improve electrical transport …”
Section: Classification Of Nanoinclusionsmentioning
confidence: 99%
“…52,85 Carbon allotropes are also famous for their use in cement and organic thermoelectric composites to improve electrical transport. 99 Fullerene was added to the thermoelectric matrixes such as skutterudite, half-Heusler, and Si−Ge compounds. Apart from reducing κ, fullerene maintains the σ with a lower reduction percentage because scattered electrons are compensated by fullerene carriers.…”
Section: ■ Classification Of Nanoinclusionsmentioning
confidence: 99%
“…Therefore, it is of significance to maximize the ZT value by enhancing the electrical transport properties (σ and α) and reducing thermal transport properties (κ). From the discovery of the Seebeck effect in carbon-fiber-reinforced concrete [ 14 ], numerous research studies have been carried out to explore various high ZT cement-based functional TE materials [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Unfortunately, the performances of most kinds of TE cement are less than 1.0 × 10 −5 due to the poor electrical transport properties of the cement matrix.…”
Section: Introductionmentioning
confidence: 99%